Human Neutrophil Elastase Proteolytic Activity in Ulcerative Colitis Favors the Loss of Function of Therapeutic Monoclonal Antibodies - Curciarello R (Dove Medical Press, 2020)
Renata Curciarello,1,2 Toni Sobande,2 Samantha Jones,2 Paolo Giuffrida,2,3 Antonio Di Sabatino,3 Guillermo H Docena,1 Thomas T MacDonald,2 Klaartje Kok2,4 1Instituto de Estudios Inmunológicos y Fisiopatológicos IIFP-CONICET, Universidad Nacional de La Plata, La Plata, Buenos Aires, Argentina; 2Centre for Immunobiology, The Blizard Institute, Queen Mary University of London, London, UK; 3First Department of Internal Medicine, University of Pavia and Fondazione IRCCS Policlinico San Matteo, Pavia, Italy; 4Barts Health NHS Trust, Royal London Hospital, London, UKCorrespondence: Klaartje Kok 4 Newark Street, London E1 2AT, UKTel +44207882 2321Fax +44 207882 2194Email klaartje.kok1@nhs.netPurpose: Proteases play an essential role in the pathophysiology of inflammatory bowel disease (IBD), contributing to the intestinal mucosal lesions through the degradation of the extracellular matrix and alteration of the barrier function. Ulcerative colitis (UC) is characterized by an extensive infiltrate of neutrophils into the mucosa and hence, increased proteolytic activity. Human neutrophil elastase (HNE) is a serine protease that has been reported to be increased in UC patients’ intestinal mucosa. Based on our previous studies, we hypothesized that HNE might induce proteolytic degradation and loss of function of therapeutic monoclonal antibodies in IBD patients.Patients and Methods: Elastase expression and elastinolytic activity were determined in mucosal explants from ulcerative colitis patients (n=6) and cultured ex vivo in the presence or absence of recombinant elafin. Enzymatic digestions of therapeutic monoclonal antibodies were performed using recombinant HNE and elafin. The integrity of the therapeutic antibodies was evaluated by immunoblotting and protein G binding assay, whereas their TNF-neutralizing activity was assessed with a reporter cell line.Results: We found that HNE and its elastinolytic activity were increased in the gut mucosa of UC patients. We also demonstrated that HNE cleaved biological drugs, impairing the TNF-α neutralizing capacity of anti-TNF monoclonal antibodies. This proteolytic degradation was inhibited by the addition of the specific inhibitor, elafin.Conclusion: Our results suggest that the high level of proteolytic degradation by mucosal neutrophil elastase, along with a potential imbalance with elafin, contributes to the loss of function of biologic agents, which are currently used in patients with IBD. These findings might explain the non-responsiveness of UC patients to therapeutic monoclonal antibodies and suggest the potential beneficial concomitant use of elafin in this treatment.Keywords: elastinolytic activity, elafin, anti-TNF, inflammatory bowel disease, biological drugs